2x-6y=2 (equation 1) and y=x-2(equation2) and we are being give the value of y in equation 2 which is x-2 so we substitute equation 2 in equation one, ie, anywhere we see y, we replace it with x-2, .2x-6(x-2)=2, we work it out and remove the bracket,ie,2x-6x+12=2, then we collect like terms, 12-2=-2+6.which is equal to 4x=10,making x the subject of the formula, we have x=2/5or 2.5, then we have known the value of x which equals 2,5, we substitute that in equation 1,we will have,Y=2.5-2=0.5,therefore x=2.5 and y=0.5